VIP‐HL: Semi‐automated ACMG/AMP variant interpretation platform for genetic hearing loss. Issue 12 (2nd September 2021) - Peng, Jiguang; Xiang, Jiale; Jin, Xiangqian; Meng, Junhua; Song, Nana; Chen, Lisha; Abou Tayoun, Ahmad; Peng, Zhiyu
Abstract: The American College of Medical Genetics and Genomics, and the Association for Molecular Pathology (ACMG/AMP) have proposed a set of evidence‐based guidelines to support sequence variant interpretation. The ClinGen hearing loss expert panel (HL‐EP) introduced further specifications into the ACMG/AMP framework for genetic hearing loss. This study developed a tool named Variant Interpretation Platform for genetic Hearing Loss (VIP‐HL), aiming to semi‐automate the HL ACMG/AMP rules. VIP‐HL aggregates information from external databases to automate 13 out of 24 ACMG/AMP rules specified by HL‐EP, namely PVS1, PS1, PM1, PM2, PM4, PM5, PP3, BA1, BS1, BS2, BP3, BP4, and BP7. We benchmarked VIP‐HL using 50 variants in which 82 rules were activated by the ClinGen HL‐EP. VIP‐HL concordantly activated 93% (76/82) rules, significantly higher than that of by InterVar (48%; 39/82). VIP‐HL is an integrated online tool for reliable automated variant classification in hearing loss genes. It assists curators in variant interpretation and provides a platform for users to share classifications with each other. VIP‐HL is available with a user‐friendly web interface at http://hearing.genetics.bgi.com/ . Abstract : This study developed a tool named VIP‐HL, aiming to semi‐automate the hearing loss ACMG/AMP rules. VIP‐HL aggregates information from external databases to automate 13 out of 24 ACMG/AMP rules specified by HL‐EP, namely PVS1, PS1, PM1, PM2, PM4, PM5, PP3, BA1, BS1, BS2, BP3, BP4, and BP7. VIP‐HL is an integrated online tool for reliable automated variant classification in hearing loss genes